Fluorescence resonance energy transfer from tryptophan to folic acid in micellar media and deionised water - Mote, U. S.; Patil, S. R.; Bhosale, Siddharth H.; Han, Sung-Hwan; Kolekar, G. B. (Journal of Photochemistry and Photobiology B-Biology, 2011)
The fluorescence resonance energy transfer (FRET) from tryptophan (Trp) to folic acid (FA) in aqueous sodiumdodecyl sulphate, cetyltrimethyl ammonium bromide, and Brij-35 as well as deionised water was investigated using steady state and time resolved fluorescence techniques. The data obtained from steady state fluorescence spectral studies and time resolved measurement indicated that the FRET from Trp to FA occurred most effectively in aqueous sodium dodecyl sulphate micellar solutions. The distance between Trp and FA were evaluated. Binding constant, number of binding sites and thermodynamic parameters were determined for Trp-FA interactions in deionised water. The values of the thermodynamic parameters suggest that the hydrophobic forces and hydrogen bonding are the key interacting forces between Trp-FA interaction. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Fluorescence quenching; Fluorescence resonance energy transfer (FRET); Folic acid; Foster theory; Stern-Volmer plot; Tryptophan